A systematic review of the efficacy and safety of Saccharomyces boulardii in the treatment of acute gastroenteritis in the pediatric population - Padayachee, Morgambal (Stellenbosch : Stellenbosch University, 2016)
Thesis (MNutr)--Stellenbosch University, 2016.